N.Y. Col. MSS, IV. 411. - (:unkn) unknown (General Publisher, 1648)
Renewed the 1645 prohibition of trade of "any munitions of War with the Indians." Punishable by death.
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES